2008
DOI: 10.1007/s10238-008-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria prevent alcohol-induced steatohepatitis in rats by acting on the pathways of alcohol metabolism

Abstract: The objective is to study the possible mechanism by which lactic acid bacteria (LAB) prevent alcohol-induced steatohepatitis in rats. A total of 25 Wistar rats were divided into three groups: a LAB-fed group, an alcohol-treated group and a control group. Both the LAB-fed group and the alcohol-treated group received alcohol (10 g kg(-1) per day) orally for up to 5 days (125 h). Before exposure to alcohol, the LAB-fed group were first treated daily with 1.5 ml/100 g of a mixture comprising 4 x 10(10) ml(-1) of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have reported on the possibility of detoxification. In line with these studies, Cell Biotech Co Ltd. and others have shown that probiotics supplementation has positive effects, alleviating acute alcoholic liver injury [5][6][7][8]20].…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have reported on the possibility of detoxification. In line with these studies, Cell Biotech Co Ltd. and others have shown that probiotics supplementation has positive effects, alleviating acute alcoholic liver injury [5][6][7][8]20].…”
Section: Discussionmentioning
confidence: 69%
“…), during pregnancy might increase the availability of ethylene glycol as a threat to fetal development and birth outcome [ 37 ]. These toxicant metabolites are generated by bacterial alcohol dehydrogenase and interact with TLR which initiate inflammation by the upregulation of IL-6, and IL-8 concentrations and processed PTB [ 38 , 39 , 40 ]. Our results showed a high level of these alcohol metabolites in the PTB < 7 d group, with significant predictive values and highly significant correlation with GAB and the CL of these metabolites, associated with PTB.…”
Section: Discussionmentioning
confidence: 99%
“…A further 41 articles were rejected based on a detailed full-text evaluation. There were 41 studies (including 37 animal studies and four clinical studies) that met the inclusion criteria after a thorough screening of the full text ( 4 , 11 , 18 56 ).…”
Section: Resultsmentioning
confidence: 99%